2014
DOI: 10.4161/bact.28364
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of T4 phage in mammalian tissues and cells

Abstract: Advances in phage therapy encourage scientific interest in interactions of phages with human and animal organisms. This has created a need for developing tools that facilitate studies of phage circulation and deposition in tissues and cells. Here we propose a new green fluorescent protein (GFP)-based method for T4 phage molecular imaging in living systems. The method employs decoration of a phage capsid with GFP fused to the N-terminus of Hoc protein by in vivo phage display. Fluorescent phages were positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…presented one of the first images of free T2 phage particles within phagocytic cells, showing phages within endocytic vacuoles that fused with denser bodies of the cytoplasm as they migrated towards the cellular interior. Similar studies have shown evidence of filamentous phage and Myoviridae within mammalian cells, although these phages were either engineered to display exogenous protein markers or the mechanism of cellular entry was not clearly delineated . Several review articles have broached the topic of phage‐epithelial transcytosis, but few attempts have been made to experimentally validate whether phage transcytosis occurs naturally and via which route .…”
Section: Across the Cell Layermentioning
confidence: 99%
“…presented one of the first images of free T2 phage particles within phagocytic cells, showing phages within endocytic vacuoles that fused with denser bodies of the cytoplasm as they migrated towards the cellular interior. Similar studies have shown evidence of filamentous phage and Myoviridae within mammalian cells, although these phages were either engineered to display exogenous protein markers or the mechanism of cellular entry was not clearly delineated . Several review articles have broached the topic of phage‐epithelial transcytosis, but few attempts have been made to experimentally validate whether phage transcytosis occurs naturally and via which route .…”
Section: Across the Cell Layermentioning
confidence: 99%
“…2B). Previous studies showed that the phage particles transferred to the interior of macrophages and significantly reduced the damage caused by the cytotoxic effects of bacteria on phagocytes (4,16). Moreover, Barr et al (13) reported that interaction of phages and mucus-producing cells does occur in the elimination of bacteria, and this interaction is based on immunoglobulin-like domains.…”
mentioning
confidence: 99%
“…Phagocytosis of T4 phage by dendritic cells was observed with green‐fluorescence protein (GFP) inserted into the phage genome. Molecular imaging of the cells containing GFP phage particles confirmed that the phage particles were successfully ingested by the dendritic cells . In addition, dendritic cells were more sensitive and responsive upon uptake of active virion particles than that of synthetic particles .…”
Section: Phage Therapymentioning
confidence: 88%
“…Molecular imaging of the cells containing GFP phage particles confirmed that the phage particles were successfully ingested by the dendritic cells. 113 In addition, dendritic cells were more sensitive and responsive upon uptake of active virion particles than that of synthetic particles. 114,115 Following the ingestion of the phages, another study using macrophages confirmed phage degradation within splenocytes, which ended up in macrophage compartments.…”
Section: Phage Therapy and The Human Immune Systemmentioning
confidence: 99%